2007
DOI: 10.1080/09500830701501823
|View full text |Cite
|
Sign up to set email alerts
|

Many body exchange effects close to the s-wave Feshbach resonance in two-component Fermi systems: is a triplet superfluid possible?

Abstract: We suggest that the exchange fluctuations close to a Feshbach resonance in a two-component Fermi gas can result in an effective p-wave attractive interaction. On the BCS side of a Feshbach resonance, the magnitude of this effective interaction is comparable to the s-wave interaction, therefore leading to a possible spin-triplet superfluid in the range of temperatures of actual experiments. We also show that the particle-hole exchange fluctuations introduce an effective scattering length which does not diverge,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…These numbers are independent of the density at unitarity so the thermodynamic scaling is just like what we found for the local model but with a smaller value for T s . We also found that when we use the s-p approximation 7,22 to construct the scattering amplitude from our Fermi liquid parameters we get better fits for some of our calculated properties. These include, T c and E b , where T c ≈ 0.14T F and E b ≈ −0.3E F .…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…These numbers are independent of the density at unitarity so the thermodynamic scaling is just like what we found for the local model but with a smaller value for T s . We also found that when we use the s-p approximation 7,22 to construct the scattering amplitude from our Fermi liquid parameters we get better fits for some of our calculated properties. These include, T c and E b , where T c ≈ 0.14T F and E b ≈ −0.3E F .…”
mentioning
confidence: 88%
“…By choosing F a 0 = 1.7 and plotting the sum of the classical and low temperature limit of the spin diffusion coefficient given by (Eq.20), we are able to present for the Fermi liquid parameter, F s 0 , and the thermodynamic scaling temperature, T s , as well as T c . In earlier publications 18,22 we used the momentum dependent induced interaction which generated Fermi liquid parameters with l > 0. In the unitary limit the induced interaction gives a small mass correction, about 15% above the bare mass, and it gives an F s 0 = −0.6.…”
mentioning
confidence: 99%
“…The crossing-symmetric method [14][15][16] [18], paramagnetic metals [16], heavy-fermion systems [19], nuclear matter [20], and ultracold atomic Fermi gases [21]. It has been known [14,19,22,23] that a consistent Fermi-liquid theory cannot be formulated in terms of short-range effective interactions alone; collective excitations generated by these must be exchanged between quasiparticles.…”
Section: A the Crossing-symmetric Methodsmentioning
confidence: 99%
“…The physics is described in terms of the Landau interaction parameters and scattering amplitudes to be discussed. In a previous study Gaudio et al [21] considered s-wave scattering by including ℓ = 0 density and spin fluctuation. We shall study s-and pwave scattering and include both ℓ = 0 density and spin fluctuations and ℓ = 1 current and spin-spin fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26], corresponding to an interaction to kinetic energy ratio of −mg 1D / 2 = 1.6. It has been recently noted [27][28][29][30] that, in the normal (non-BCS condensed) phase, the intra-species interaction can be strongly modified (and in particular turned attractive) by the polarization of the medium. As a consequence, at sufficiently low temperatures, normal phases are unstable against the formation of intra-species p-wave superfluids.…”
mentioning
confidence: 99%